Determinants of Qris Usage Decisions in Culinary MSMEs Using the TAM Model - Tengku Muhammad Rafly Rachman; Isnaini Harahap; Juliana Nasution (Academia Open, 2025)
Background: The rapid digitalization of payment systems in Indonesia presents a transformative opportunity for Micro, Small, and Medium Enterprises (MSMEs), yet adoption remains uneven. Specific Background: In particular, culinary MSMEs in Medan City exhibit varied levels of engagement with QRIS (Quick Response Code Indonesian Standard), despite its potential to streamline transactions and enhance financial inclusion. Knowledge Gap: Limited empirical evidence exists on the behavioral drivers influencing QRIS adoption from an Islamic financial perspective, especially within the context of MSMEs. Aim: This study aims to examine the determinants of QRIS adoption among culinary MSMEs in Medan using the Technology Acceptance Model (TAM) framework. Results: Using a quantitative approach involving 78 purposively sampled MSMEs and multiple linear regression analysis, the study reveals that perceived usability and Islamic financial literacy significantly and positively influence QRIS adoption, while perceived convenience unexpectedly has a negative effect. These variables collectively explain 36.8% of the variance in adoption behavior. Novelty: The integration of Islamic financial literacy into the TAM framework presents a novel analytical perspective within the fintech adoption discourse in emerging markets. Implications: To promote broader QRIS adoption, policymakers and financial institutions should prioritize educational interventions addressing perceived convenience and enhance digital literacy rooted in Islamic financial principles. Highlight: Usability and Islamic literacy drive QRIS adoption. Convenience negatively affects adoption behavior. 36.8% of adoption decision explained by key TAM variables. Keywords: QRIS Adoption, Islamic Financial Literacy, TAM Framework, Culinary MSMEs, Digital Payment